The Time Value of Money and the Economic Value of Time (A Comparative Study) - Rabbani, Mohammad Fathi; Hasan, Asyari (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
“A dollar today is worth more than a dollar tomorrow because a dollar today can be invested to get a return”. This sentence has made the function of money which was originally a medium of any transactions turned into commodities for getting any returns. By TVM, productivity and efficiency in investment and business can be measured. However, TVM on the Islamic viewpoint is closely related to interest. The objection of this study is to analyze critically the concept of the time value of money and its relation to interest, as well as the solution that has been offered. This paper is qualitative research with a literature approach based on primary data. The deductive method is used for collecting any data related to the topic of research, while the inductive method is used to describe the findings from primary data. The results of this study indicate that there are several rationalities for implementing TVM in the financial system including time preference, interest, risk bearing, uncertainty, and inflation that arise in society. The implication is, that any rationality that arises from the implementation of TVM must be followed by economic activities that occur in society. In this case, the economic value of time plays a role in separating natural certainty contracts and natural uncertainty contracts. This separation ultimately has implications for the elimination of gharar and interest in contracts.